PENYUSUNAN STANDAR OPERASIONAL PROSEDUR PADA OPERASIONAL TOKO DI SUPERMARKET UFO (UNITED FASHION OUTLET) SURABAYA - HANDOKO, LIONISIA MERDEKAWATI (Universitas Katolik Widya Mandala Surabaya, 2012)
The development of retail increases rapidly giving an impact in the increasing competition of market share. This result is the company will be required to maintain the position and strength in order to compete in the retail world. The company's activities can not be separated from a variety of transactions for compliance activities of the company providing the goods are sold to meet the needs of the community. In the achievement indicators of a company to full fill the society’s needs, so that all activities performed by employees goes well we need a rule which becomes the basis of the employeement in doing a job that called Standard Operating Procedure (SOP). The major purpose of the implementation of the SOP is to avoid mistakes in the execution of a work process that can result in shrinkage. PT. Darmo Lestari Sentosa which has familiar name with the UFO (United Fashion Outlet) are factory outlets and supermarkets. In the process of apprenticeship did the observation and analysis on the operational deployment of the store by doing a questionnaire so that we can know how much knowledge of employees about the SOP. From the results of observation and questionnaire, known major causes SOP owned PT. Darmo Lestari Sentosa is the development of SOP is still not well structured and lack of socialization by superiors. From the results of the questionnaire, the company can make efforts to maximize the implementation of the SOP that has been made.